Successful treatment of multiple plantar warts complicated by systemic lupus erythematosus with ALA-PDT, a case report - Fangfang Wang; Lingzhi Li; Suling Xu (Photodiagnosis and Photodynamic Therapy)
Plantar warts are common skin neoplasms caused by human papillomavirus (HPV) infection. Patients with immunocompromised conditions often have a higher prevalence of HPV infection-induced skin warts, with recalcitrant nature to various options of treatment. Here, we diagnosed a case of multiple and coalesced plantar warts complicated by Systemic Lupus Erythematosus (SLE) which persisted for years and was refractory to conventional treatment. Following superficial shaving to remove the thickened corneum, we initiated 5-aminolevulinic acid - photodynamic therapy (ALA-PDT). After four rounds of the treatments within two months, the lesions were completely cleared with no recurrence in one year of follow-up.